E-Learning in Anatomy: Medical Students' Perspectives on Synchronous and Asynchronous Lab Sessions - Farsal, Ryzufar Altarif; Oktavia, Nandina; Nasution, Gita Tiara Dewi; Rahman, Putri Halleyana Adrikni (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: The Covid-19 pandemic has become a global health disaster, various sectors have been affected including the education sector. Online learning is then carried out as an alternative solution to carry out learning. This online learning is carried out in all elements of education including Universities. The intended online learning is divided into two methods, asynchronous and synchronous methods. The difference in these methods will certainly lead to different perceptions for each student, especially in anatomy laboratory learning.This stud aimed to find out the perception of Unpad Medical Faculty students towards the asynchronous and synchronous method of online anatomy laboratory learning..Methods:This research is a quantitative cross-sectional descriptive studies and involved 129 respondents from student of Unpad Faculty of Medicine students class of 2019. This was done using Google Forms which contained a questionnaire and informed consent sheet.Results: FK Unpad online anatomy laboratory learning falls under good category, with each index value: perception of learning experience: 76.2%, perception of lecturer capabilities: 77.1%, perception of facilities and infrastructure: 83.7 %.Conclusion: Online anatomy laboratory learning can still be continued by combining both asynchronous and synchronous methods, so that learning can take place more effectively.